A comparative study to assess the awareness of antibiotic resistance amongst first and second year medical undergraduate students in a medical college - V. D., Bharath Kumar; L., Kalpana (International Journal of Basic & Clinical Pharmacology, 2018)
Background: With the rising instances of antibiotic resistance and decline in the discovery of newer antibiotics, it is high time to prevent the emergence of antibiotic resistance. One of the best measures regarding the above problem is education and creating awareness regarding antibiotic resistance, and that too primarily among healthcare professionals. The initiation should start at the basic level and that too in the early days of medical profession, so that there is greater awareness and strong foundation for antibiotic prescribing pattern. The present study is taken up to compare awareness among 1st year and 2nd year medical students in a private medical college with 2nd year medical students having prior education regarding antibiotics resistance and first year students representing general public without any education regarding antibiotics resistance. Methods: This study was a comparative, cross-sectional, questionnaire based study. The questionnaire was validated for face validity and content validity from subject experts. The two groups selected were 1st year and 2nd year medical undergraduates. Data was analysed using simple descriptive statistics. Results: 136 students from 1st year and 88 students from 2nd year participated in the study. In both the groups studied, majority of the respondents completed the full course of antibiotics. 77% of 1st year and all 2nd year students were aware of the antibiotic resistance. 99% of 2nd year students and only 49% of the 1st year students were aware of the reasons for it (p<0.01). Awareness regarding prophylactic usage of antibiotics, usage for simple common cold and usage of higher antibiotics for mid infection leading to Antibiotic Resistance was significantly less among first year students. 2nd year students were well aware of consequences of antibiotic resistance like ineffective treatment, prolongation of illness, emergence of bacterial resistance and additional cost burden than 1st year students. Awareness regarding other aspects of antibiotic resistance was not significant between two groups. Conclusions: Stressing upon awareness and education regarding antibiotic resistance in the early days of medical curriculum will help in change of behaviour and habits of antibiotic usage and rational prescribing of antibiotics by the future doctors.